PENGARUH PENERAPAN AKUNTANSI LINGKUNGAN FISIK DAN AKUNTANSI LINGKUNGAN MONETER TERHADAP KINERJA LINGKUNGAN PADA RSUD MOHAMMAD NATSIR, RSUD Dr. ACHMAD MOCHTAR DAN RSUD PARIAMAN - Wira Mofa; Siska Yulia Defitri; Juita Sukraini (Universitas 45 Surabaya, 2023)
This study aims to determine how much influence the application of physical environmental accounting and monetary environmental accounting has on environmental performance at Mohammad Natsir Hospital, Dr. Achmad Muchtar and Pariaman Hospital. This research was conducted in 3 hospitals, namely Mohammad Natsir Hospital, Dr. Achmad Muchtar and Pariaman Hospital. The hospital is a hospital whose waste management does not yet use an Incinerator, but still uses the services of a third party, thus requiring the application of good environmental accounting. The sampling technique in this study used total sampling which was conducted randomly. The data of this study include primary data obtained through the distribution of questionnaires to 100 respondents at the Mohammad Natsir General Hospital, Dr. RSUD. Achmad Muchtar and Pariaman Hospital. The statistical test used is multiple regression analysis. Based on the results of statistical analysis, it can be concluded that partially physical environmental accounting has a significant effect on environmental performance, this is evidenced by the distribution of the t-value with tcount 7.017 > ttable 1.984 and a significant value of 0.00 <0.05. Monetary environmental accounting has a significant effect on environmental performance, this is indicated by the distribution of the t value with tcount being 2.863 > ttable 1.984 and a significant value of 0.05 <0.05. Simultaneously, physical environmental accounting and monetary environmental accounting have a significant effect on environmental performance, this is indicated by the F test value with Fcount 37.265 > Ftable 2.70 and a significant value of 0.000 which is smaller than the targeted significance level of 0.05. The coefficient of determination R Square R2 is 0.434 or 43.4%. This indicates that the contribution of the accounting variables of the physical environment and the monetary environment to environmental performance is 43.4%. While the remaining 56.6% is influenced by other variables outside the model.